Case Studies in Biocultural Diversity from Southeast Asia Traditional Ecological Calendars, Folk Medicine and Folk Names - Franco, F. Merlin; Knudsen, Magne; Hassan, Noor Hasharina (Asia in Transition,, 2022)
This open access book demonstrates the linkages between local languages, traditional knowledge, and biodiversity at the landscape level in Asia, providing a fresh approach to discussions on Asia's biocultural diversity. The book carries forward earlier analyses but importantly focuses on 'traditional ecological calendars,' 'folk medicine,' and 'folk names' in the context of the vital importance of maintaining biological, cultural, and linguistic diversity. It does this by addressing a range of cases and issues in relation to Southeast Asia: Brunei Darussalam, Indonesia, Malaysia, the Philippines, and North-East India. The several chapters demonstrate the ways in which the various forms of knowledge of the environment and its categorizations are important in areas such as landscape and resource management and conservation. They also demonstrate that environmental knowledge and the practical skills which accompany it are not necessarily widely shared. This book sends important messages to those who care about the sustainability of our environment, the maintenance of its biocultural diversity, or at least the maintenance of what remains of it because much has changed. This interdisciplinary collection draws from a wide range of disciplines and is of appeal to students and scholars in anthropology, environmental studies, geography, biodiversity, and linguistics.